Keefektifan Strategi Crossword Puzzle Terhadap Hasil Belajar Bahasa Indonesia Siswa - Ervinasyah A; Muhammad Irfan; Hastuti Hastuti (Universitas Negeri Makassar, 2024)
The problem in this research is whether the influence of the Crossword Puzzle Strategy is effective on the Indonesian language learning outcomes of class III students at SD Negeri 20 Tala-Tala. This research aims to determine the effectiveness of the Crossword Puzzle Strategy on the Indonesian language learning outcomes of class III students at SD Negeri 20 Tala-Tala, which can be seen from four aspects, namely Indonesian language learning outcomes, student activities, student responses, and implementation of learning. This type of research is pre-experimental research involving one class as the experimental class. The research implementation procedure includes an initial test (pretest) and a final test (posttest). The subjects in this research were 26 class III students at SD Negeri 20 Tala-Tala. The results of the research show that the Crossword Puzzle Strategy is effective on the Indonesian language learning outcomes of class III students at SD Negeri 20 Tala-Tala. This can be seen from the comparison between the pre-test and post-test scores. The average pre-test value obtained was 34.60. The average value was in the interval 0-49 which was included in the very low category. Meanwhile, the average post test score obtained was 92.30, which is in the 90-100 interval, which means it is in the high category. Apart from that, t-test calculations were also used. The research results were obtained. So it can be concluded that H 0 is rejected and H 1 is accepted. This means that the use of the Crossword Puzzle strategy is effective on the Indonesian language learning outcomes of class III students at SD Negeri 20 Tala-Tala.